Dearth of electrophysiology fellows: perspectives from cardiology fellows‐in‐training. Issue 8 (20th July 2022) - Patel, Harshil; Zughaib, Marc; Rajpurohit, Dhruv; Whitler, Cameron; Kalaba, Frank; Bradley, Christopher; Zughaib, Marcel
Abstract: Background: Over the last 6 years, there has been a high percentage of unfilled cardiac electrophysiology (EP) training spots each year. The authors aimed to investigate potential explanations for the unfilled positions based on a survey from the current Fellows‐In‐Training (FITs). Methods: An attempt was made to reach the current cardiology FITs across all programs of the U.S. via email. An anonymous questionnaire was created consisting of 14 questions. Questions posed were regarding factors affecting each participant's interest in or lack of pursuing an EP fellowship. Descriptive statistics of the responses were performed. Results: A total of 26% (35/134) respondents expressed their interest in applying to an EP fellowship. The most common reasons to apply to EP were: Interest in EP, procedural specialty, and work‐life balance. Of the 99 respondents that were not applying to EP, the most common reasons not to apply were: Less interest in EP, two‐year training duration, and complexity of the specialty. The top reasons for the fellows to believe there is a dearth of EP FITs were: two‐year training duration, lack of interest in EP, and the complexity of the specialty. The changes that would encourage EP fellowship interest were: More exposure to EP training during general cardiology fellowship, shortening the EP training duration, and having more information available regarding employment opportunities. Conclusion: The study was able to identify factors responsible for vacancies in EP fellowship positions from the view of current cardiology FITs. Stakeholders at the national level involved in framing policies related to fellowship education would be able to utilize this information to address the shortage of EP FITs and increase recruitment to EP fellowships.